1976
DOI: 10.1095/biolreprod14.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Capacitation of Hamster Spermatozoa With Adrenal Gland Extracts

Abstract: The hamster adrenal gland was found to be a new and very potent source of "sperm motility factor" (SMF); the activity of SMF in adrenal extracts was approximately 100 to 200 times that in hamster blood serum.Hamster

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…of 4 observations) significantly different from those of respective control without A23187 (P < 005). Effects of tissue extracts on sperm cyclic nucleotide levels Hamster serum and adrenal extracts have been reported to contain a substance of low molecular weight which stimulates hamster sperm motility (Bavister, Yanagimachi & Teichman, 1976). In the present study only sea urchin FRE caused an elevation in sperm cyclic AMP levels (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…of 4 observations) significantly different from those of respective control without A23187 (P < 005). Effects of tissue extracts on sperm cyclic nucleotide levels Hamster serum and adrenal extracts have been reported to contain a substance of low molecular weight which stimulates hamster sperm motility (Bavister, Yanagimachi & Teichman, 1976). In the present study only sea urchin FRE caused an elevation in sperm cyclic AMP levels (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Until recently it was impossible to analyze ion requirements for some aspects of the physiology of hamster gametes and fertilization because of the lack of chemically defined media that supported sperm capacitation and fertilization. This is now possible, thanks to the endeavor by Meizel, Bavister, and their associates [Bavister et al, 1976;Cornett and Meizel, 1978;Meizel et al, 1980;Leibfried and Bavister, 19811, who developed semi-chemically defined media that support capacitation and acrosome reaction of spermatozoa as well as fertilization in the hamster. a supporting capacitation and acrosome reaction of spermatozoa.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the dialyzable factor can be replaced by a "motility factor" of less than 1000 molecular weight obtained from extracts of hamster adrenal gland (10) or hamster, guinea pig, or human spermatozoa (11,12). The motility factor derived from spermatozoa also seems to maintain hamster sperm viability upon dilution in vitro (12).…”
mentioning
confidence: 99%